The super achiever - D'cruz, Neville (The Star, 2012)
There is nothing to stop Malaysian scholar Michael Chin from getting what he wants both academically and professionally. MALAYSIAN scholar is making waves as part of a growing tide of students who have taken their education to the global classroom.